Income Risk, Coping Strategies, and Safety Nets - Dercon, Stefan (World Bank, 2013)
Poor rural and urban households in developing countries face substantial risks, which they handle with risk-management and risk-coping strategies, including self-insurance through savings and informal insurance mechanisms. Despite these mechanisms, however, vulnerability to poverty linked to risk remains high. This article reviews the literature on poor households use of risk-management and risk-coping strategies. It identifies the constraints on their effectiveness and discusses policy options. It shows that risk and lumpiness limit the opportunities to use assets as insurance, that entry constraints limit the usefulness of income diversification, and that informal risk-sharing provides only limited protection, leaving some of the poor exposed to very severe negative shocks. Public safety nets are likely to be beneficial, but their impact is sometimes limited, and they may have negative externalities on households that are not covered. Collecting more information on households vulnerability to poverty through both quantitative and qualitative methods can help inform policy.